Feeding Precarity Between State and Capital: Women Workers and Breastfeeding in Cakung Manufacturing Industry - Shabia, Gusti Nur Asla (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
Women constitute the vital workforce in Indonesia's economy, particularly in sectors like garment, textile, and footwear. Despite their economic importance, these industries are characterised by excessive control, pressure, and violence, transforming women into cheap labour and limiting their lives both in the production and social reproduction realm. This study analyses how the discipline of factory work has implications for women workers in their care work, specifically in breastfeeding. Through a qualitative approach, this study uses focus group discussions (FGD) and interviews with women garment and textile industry workers in Kawasan Berikat Nusantara, North Jakarta. The study also analyses the state's response and position in child-feeding matters. The study shows how the regimented nature of factory work, which controls the energy, time, and bodies of women workers, coupled with the absence of job security and protection from the state, limit workers’ capacity to care for their families, particularly to breastfeed their children. Consequently, women workers have to switch to formula milk. I argue that the workers’ reliance on formula milk illustrates a form of neoliberalism in which the state subjugates women workers to the capitalist economy both in the realms of production and social reproduction, forcing them to live in a precarious condition. This potentially will cause health, nutrition, and other quality of life problems for mothers and children in the future.